PERUBAHAN PARADIGMA JASA PELAYANAN KESEHATAN RUMAH SAKIT DAN REKOMENDASI KEBIJAKAN STRATEGIS BAGI PIMPINAN =THE PARADIGM CHANGE OF HOSPITAL SERVICES ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The paradigm of hospital services has changed fundamentally, in which hospital has become an enterprise, which has many strategic business units. The natural change of the environment will encourage hospitals to become organization characterized by multi product and mixed output so that handling with management concept will be needled. Hospital has four stakeholders who need to be taken into account, i.e. employees or providers, owners, patients as the consumers and society. Every stakeholder expect responsibility from the management or administrator who constitute the value and credibility for the stakeholder especially for the trust given. Hospitals are faced with two contradiction conditions, i.e. giving the best health services in carrying out their social function, and paying attention to economics principles in order to get profit. Hospital leader must decide policy direction for the ongoing development of the hospital. The decision made must be strategic, which can make use of synergy in the hospital and also use opportunity and minimize risk that will happen. Some recommendation of strategic policies for hospital leader include recommendation for increasing society attitude toward health, increasing hospital services competitiveness, increasing health cost and efficiency and sustainability of technology and quality. Keywords: competitiveness